Describing advertising approach by Ministry of Health Malaysia for public service announement campaign: case study on anti dengue campaign in Press AD / Norsharina Samsuri and Anith Liyana Amin Nudin - Samsuri, Norsharina; Amin Nudin, Anith Liyana (2016)
The Ministry of Health Department had put in a lot of effort in promoting a better lifestyle among Malaysia society through public service announce campaign that include anti-dengue campaign throughout media, but the public doesn't care and less participated in efforts to eliminate and reduce the cases of dengue fever that gong increase yearly. The government has spent almost RM 1.7 million in 2010 for media promotion in providing information about aedes mosquito that involves various approaches, most of them are emotional appeal, and it clearly applies in educating people about prevention, treatment and awareness as a vector that carries dengue virus. All this approach is objectively to ask public in adopting positive attitude to prevent the issue. The purpose of the study is to analyze and determine the advertising• approach on existing anti dengue camping by Department of Health Promotion in Ministry of Health Malaysia. To conduct this study, a mixed method approach was employed which encompasses a visual analysis by referring to advertising category and a consumer perception survey. In the first stage, sanlples of anti-dengue calnping approach being analyze and highlighted Facts, Motivation & Inspiration, Life Experience and The Problenl is the Solution are the• most frequently approach apply in the camping In the second stage, conducting a survey towards public perception on Knowledge on aedeses Mosquito as vector. beliefs toward dengue prevention. Attitude on prevention behavior. Interpretation on Visual Message.